A comparative study between submandibular-facial artery island flaps (including perforator flap) and submental artery perforator flap: A novel flap in oral cavity reconstruction. (December 2019) - Ou, Xin-rong; Su, Tong; Huang, Long; Jiang, Can-hua; Guo, Feng; Li, Ning; Min, An-jie; Jian, Xin-chun
Highlights: Submandibular-facial artery island flap (S-FAIF) is a robust, reliable and easy-acquired novel flap. S-FAIF includes conventional flap based on level II facial artery perforator (FAP) and authentic level I FAP flap. The first case series of authentic level I FAP flap. S-FAIF is preferred to submental artery perforator flap when hair problem is considered. S-FAIF is an excellent addition to reconstructive tools in intraoral reconstruction. Abstract: Objective: The purpose of this study was to introduce submandibular-facial artery island flaps (S-FAIF), including the perforator flap, and to evaluate their application for intraoral reconstruction in comparison with submental artery perforator flaps (SMAPF). Methods: Ninety-six patients who underwent intraoral reconstruction using an S-FAIF (n = 34) or SMAPF (n = 62) after cancer resection were recruited in this study. The flap characteristics (viz., pedicle length, flap size, venous drainage pattern, and harvest time), short-term outcomes (viz., flap partial loss, intraoral wound dehiscence, fistula, and wound infection), and long-term morbidity (viz., facial nerve palsy, neck motion restriction, and hair growth) were compared. Results: Nine S-FAIFs were authentic perforator flaps pedicled by level Ⅰ facial artery perforators, while the rest were island flaps based on level Ⅱ facial artery perforators. The survival rates of S-FAIF and SMAPF were both 100 percent. Flap partial loss occurred in two patients in each group. The pedicle length of S-FAIF was shorter than that of SMAPF ( p < 0.001). Statistics analysis revealed no significant difference regarding flap size, venous drainage pattern, short-term outcomes, neck motion restriction, or facial nerve palsy between the groups. S-FAIF required less harvest time ( p < 0.001) and experienced less hair growth when compared to SMAPF ( p = 0.011). Conclusions: The S-FAIF is a robust and reliable novel flap and on par with SMAPF for reconstruction of small and medium-sized intraoral defects. It is preferred to SMAPF when technical requirements for flap harvest and hair problems are considered. It should be supplemented to the armamentarium for intraoral reconstruction.